MEDICAL STUDENTS’ PREPARATION FOR ANALYSIS OF STUDY MATERIALS IN THE CHEMICAL COURSE - Kazuša, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The ability to reproduce and assess the content of the text and its argumentation is the most important competence in any profession. Medical students’ systematic approach to information analysis based on evidence-based medical principles can be already developed at the beginning of the study process in the theoretical courses. The goal of this research is to analyse the effectiveness of a didactic model that is based on critical thinking principles and includes a wide range of approaches to working with information. Learning by memorization has become dominant for medical students in Rīga Stradiņš University (RSU). The goal of the chemistry course is to shift the emphasis from fact memorization to knowledge construction, thus significantly changing students’ analytic abilities. The chemistry course not only creates the conditions for understanding content but also improves skills in various methods of acquiring knowledge. When new knowledge is being constructed students learn methods for organizing and structuring information and each student has an opportunity to choose the appropriate amount of information and participation level. Study material is being analyzed sequentially from the simplest to the most complex i.e. by starting with elementary calculations and moving to integrate information from different disciplines. Didactic model based on critical thinking principles underpins "logical steps" and requirements (fact recognition, analysis, and interpretation, recognition of fallacies and concepts, the perfection of reasoning algorithms, interdisciplinary connections) orient students to critically evaluate information while searching for problem solutions. The results obtained in student surveys and final tests prove that the created model, which is based on critical thinking principles, ensures successful mastering of the chemistry course to students with any level of prior knowledge.